First report of Ug99 Wheat Stem Rust caused by Puccinia graminis f. sp. tritici in South Asia - Patpour, Mehran; Baidya, Suraj; Basnet, Roshan; Justesen, Annemarie Fejer; Hodson, Dave; Thapa, Dhruba; Hovmøller, Mogens Støvring (Plant disease, 2024)
Since the emergence of Ug99 wheat stem rust in Uganda in 1998 (Pretorius et al. 2000), the threat of movement into South Asia has been a concern due to long-distance dispersal capacity of airborne spores (Brown and Hovmøller 2002; Singh et al. 2008; Meyer et al. 2017). Increased preparedness by comprehensive rust surveillance efforts and development and deployment of resistant cultivars in advance of an incursion into South Asia has been one of the success stories of the Borlaug Global Rust Initiative (Sharma et al. 2013). In November 2023, an off-season rust survey was conducted in Marpha, Gandaki and Bagmati provinces in Nepal. Rust was only observed at two sites, Dangdunge of Dolakha district and Mude of Sindhupalchok district, where spring wheat was grown as fodder crop outside the main cropping season. Rust infected wheat leaves (10-15 leaves per site) were air dried and sealed in envelopes that were shipped under permit to the Global Rust Reference Center, Denmark. Bulk samples of stem rust, Puccinia graminis f.sp. tritici (Pgt), were recovered from both envelopes, and single pustule isolates were raised and multiplied on Morocco and McNair. Meanwhile, specimens of dry leaves were subjected to SSR genotyping according to standard procedures (Patpour et al. 2022). One distinct multi-locus Pgt genotype was observed, identical to and representing 99% of Ug99 isolates within Clade I collected in East Africa between 2012-2022. A Pgt single pustule isolate from each of the sampling sites were inoculated onto 20 internationally agreed stem rust differential lines using standard procedures, and 14 supplementary lines providing additional resolution of pathogen virulence (Patpour et al. 2022). The pathotyping was repeated in two independent experiments, which resulted in the infection type pattern of Pgt race TTKTT (Supplementary Table 1). Additional independent SSR genotype assays of recovered isolates confirmed the prevalent genotype of Clade I (Patpour et al. 2022; Szabo et al. 2022). This first detection of Ug99 race TTKTT in South Asia emphasizes the need for continued coordinated international surveillance efforts and utilization of diverse sources of resistance to control stem rust in wheat. New surveillance efforts in Nepal during February-March 2024 did not reveal additional cases of wheat stem rust. However, more detailed and sustained rust surveillance efforts, assessment of the vulnerability of current wheat crops to Ug99 and other races of stem-, stripe/yellow- and leaf rust, as well as intensified breeding for rust resistance throughout the region is strongly recommended to meet current and future plant health risks.